Is the knowledge about the wild birds influenced by the socioeconomic conditions of the human populations? - Santos, Surane da Silva Nogueira; Guerreiro Martins, Cláudia Sofia; Martins, Flávia de Campos (Ethnobiology and Conservation, 2020)
The human populations of the Brazilian semiarid region interact strongly with the avifauna throughout the entire occupation of its territory. These interactions were established in a context of adverse edaphoclimatic conditions that limited farming production and socioeconomic welfare, making the use of birds as food and income generators excuses as an important subsistence resource. Therefore, it is relevant to know whether such interactions today are still influenced by socioeconomic factors and in what way. Semi-structured interviews were applied to 105 residents, 45 men and 60 women, in rural communities of Casa Nova, Bahia state. Correlation analysis and regression models were performed to verify how the socioeconomic variables ‘gender’, ‘age’, ‘education’, ‘monthly income’ and ‘residence time’ in the region explain the variation in the number of known species and the acknowledgement of the ecological importance of the birds. The respondents made 840 bird citations, corresponding to 60 species. There was a correlation between the socioeconomic factors (age, income, residence time in the region) and the number of species mentioned, but there was no correlation with the acknowledgement of the ecological importance of the species, probably because few people knew how to answer to that question. Men cited significantly more bird species than women. The results also indicate a low level of knowledge about bird species among younger populations. Socioeconomic factors strongly influence people’s knowledge of bird species in their region. Exposure to and experience with wild birds, gender, education and income together influence the knowledge about the diversity of this group.